DIMENSI SUFISTIK KITAB ASRÂR ASH-SHALAH MIN ‘IDDAH KUTUB MU’TAMIDAH - Mumtaz Hakimi; Ahmad Syadzali (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2017)
The study examines the dimensions of Sufism in the book of Asrâr ash-Shalah Min 'Iddah Kutub Mu'tamidah written by Abdurrahman Siddiq Al-Banjari. The method used in this study is a qualitative approach that is an approach to generate descriptive data in the form of written words because this study seeks to describe elements of Sufism contained in the book of Asrâr ash-Shalah Min 'Iddah Kutub Mu'tamidah written by Abdurrahman Siddiq al -Barari. The results of this study indicate that the elements of Sufism contained in that book is ethical and philosophical Sufism.